The question of theological truth: philosophical and interreligious perspectives - Depoortere, Frederiek; Lambkin, Magdalen (Currents of encounter, 2012)
Preliminary Material -- Editors’ Introduction /Frederiek Depoortere -- Introducing the Question of Theological Truth /Frederiek Depoortere -- Theological Truth in the Context of Modern Philosophy /Olivier Riaudel -- Theological Truth in the Context of Contemporary Continental Thought: The Turn to Religion and the Contamination of Language /Lieven Boeve -- The Liturgical Enactment of Truth /Michael Purcell -- Religious Truth: Seeing Things as They Really Are Experience, Insight, and Religious Stories /Hendrik M. Vroom -- Meaning and Truth in the Dialogue between Religions /Catherine Cornille -- Lindbeck and Ricoeur on Meaning, Truth, and the Translation of Religions /Marianne Moyaert -- Theological Truth from the Perspective of an Interreligious Hermeneutics of Love /Werner G. Jeanrond -- The Issue of Truth as it Arises from the Praxis of Scriptural Reasoning /Magdalen Lambkin -- The Plight of Truth in Hindu Christian Hermeneutics /Martin Sebastian Kallungal -- Theological Truth and Dialogue: A Buddhist Christian Perspective /Rose Drew -- The Question of Theological Truth in a Multireligious World: Reflections at the Interface of Continental Philosophy and Interreligious Studies /Frederiek Depoortere -- Index of Names -- Index of Subjects -- Contributors to this Volume.